ANALISIS HARGA TIKET DAN FASILITAS TRANSAKSI TERHADAP KEPUASAN PENUMPANG KERETA API BANDARA SOEKARNO HATTA - Khairunnisa, Khairunnisa; Yoeliastuti, Yoeliastuti; Wibowo, Edi Wahyu (POLITEKNIK LP3I JAKARTA, 2019)
In the era of transportation development and technological sophistication, people tend to choose fast and affordable transportation. To meet the needs of the people the Soekarno Hatta Airport Railway has officially operated. Some problems have been complained by passengers, namely regarding ticket prices and facilities. The influence of Ticket Prices on the satisfaction of railroad passengers of Seekarno Hatta Jakarta Airport based on statistical results can be said that the passengers of Soekarno Hatta Jakarta Airport Railroad have a significant partial satisfaction for using Airport Railway in accordance with the Ticket Prices that have been paid. Satisfaction with ticket prices paid is due to affordable prices, benefits received, suitability to facilities, distance traveled, travel time. The effect of the Facility on the satisfaction of railroad passengers of Soekarno Hatta Jakarta Airport based on statistical results can be said that Soekarno Hatta Jakarta Airport Railway passengers have a significant partial satisfaction for using Airport Railway in accordance with the Facilities received. Satisfaction with facilities received such as parking lots, waiting rooms, free toilets, places of worship, supporting facilities. While the Effect of Ticket Prices and Facilities on the satisfaction of railroad passengers of the Soekarno Hatta Jakarta Airport based on statistical results it can be said that the passengers of the Jakarta Soekarno Hatta Airport Train have significant simultaneous satisfaction to use the Soekarno Hatta Airport Jakarta Train in accordance with Ticket Prices, Facilities and Ease Perceptions Transaction. The satisfaction of Soekarno Hatta Airport Railroad passengers on Ticket Prices, Facilities and Transaction Ease Perceptions that are jointly felt are satisfaction of punctuality, satisfaction of completeness of facilities, satisfaction of price suitability, satisfaction of departure schedules, and satisfaction of functions and facilities.Keywords: Airport Railway, Satisfaction, Ticket Prices, Facilities